Inflation in the euro area: Factors mostly have only a temporary effect, but risk of prolonged elevated inflation remains - Kerstin Bernoth; Gökhan Ider (DIW Weekly Report, 2021)
Headline inflation in the euro area jumped to more than three percent in the summer after years of relatively low inflation rates well below the target of close to but below two percent set by the ECB until July 2021. One of the main reasons for the rise in inflation is the increase in energy prices since the beginning of 2021. However, there are further indications that inflation in the euro area will remain elevated in the coming months. This report analyzes the factors that could have an impact on inflation. However, most of these factors, such as the fiscal stimulus and pent-up demand only have temporary effects. Others, such as the unemployment gap, weigh less severely than expected. A change in inflation expectations, which could trigger a wage-price spiral, poses the main risk for a prolonged period of elevated inflation. While these expectations are still in line with the inflation target, the ECB should keep a critical eye on their development and, if necessary, take decisive action to maintain its credibility.
Keywords: E31; E52; E58; 330; Inflation; inflation expectations; monetary policy